Skirtboarder net-a-narratives: Young women creating their own skateboarding (re)presentations. (April 2013) - MacKay, Steph; Dallaire, Christine
By creating and posting their own stories on the Internet, sportswomen are able to challenge the persistent, sexist, mainstream and alternative (skateboarding) media (re)presentations of female athletes. A Foucauldian discourse analysis of 262 posts of the Skirtboarders' blog – a Montreal-based, Canadian female skateboarding crew's Internet project – explores the ways in which a group of sportswomen circulate alternative discourses of femininity. In these (re)presentations, the Skirtboarders embrace various femininities and, at the same time, reject binaries (male/female) without explicitly claiming a feminist agenda or attaching themselves to other oppositional discourses. This indicates a third-wave feminist sensibility. The Skirtboarders reproduce some normative discursive fragments commonly found in media (re)presentations. Furthermore, they post links to mainstream and alternative media coverage of their crew, which at times reflects the 'problems' of historical media coverage (sexualization, marginalization and trivialization). However, most of their online productions portray them as polygendered skaters (action shots, skating activities and lifestyle) and are thus radically different. The Skirtboarders' discursive portrayals of female skateboarders are therefore uniquely alternative to other media (re)presentations but at the same time, paradoxical.